The many faces of expatriate identity. (November 2015) - Adams, Byron G.; van de Vijver, Fons J.R.
Abstract: With the advent of globalization, the number of expatriates within the international labor force is continuously increasing. While expatriate acculturation and adjustment receive much empirical and theoretical attention, less attention is afforded to expatriate identities. Expatriates, compared to other migrant workers, have more options to deal with acculturation and identity issues. We conceptualize expatriate identity by linking acculturation and a tridimensional model of identity (personal identity, relational identity, and social identity). We argue that expatriate identity, which is important for psychosocial adjustment and well-being, can take on two forms: a more cosmopolitan perspective, which expatriates develop after much experience in various cultures and a more pragmatic perspective in which expatriates maintain their original identity and make only superficial adjustments to a new context. We provide recommendations for future research as well as implications for organizations.